ZmmiR169q/ZmNF-YA8 is a module that homeostatically regulates primary root growth and salt tolerance in maize - Xing, Lijuan; Zhang, Lan; Zheng, Hongyan; Zhang, Zhuoxia; Luo, Yanzhong; Liu, Yuan; Wang, Lei (Frontiers in Plant Science, 2023)
In response to salt stress, plants alter the expression of manifold gene networks, enabling them to survive and thrive in the face of adversity. As a result, the growth and development of plant roots could be drastically altered, with significant inhibition on the growth of root meristematic zones. Although it is known that root growth is primarily regulated by auxins and cytokinins, the molecular regulatory mechanism by which salt stress stunts root meristems remains obscure. In this study, we found that the ZmmiR169q/ZmNF-YA8 module regulates the growth of maize taproots in response to salt stress. Salt stress downregulates ZmmiR169q expression, allowing for significant upregulation of ZmNF-YA8, which, in turn, activates ZmERF1B, triggering the upregulation of ASA1 and ASA2, two rate-limiting enzymes in the biosynthesis of tryptophan (Trp), leading to the accumulation of auxin in the root tip, thereby inhibiting root growth. The development of the maize root is stymied as meristem cell division and meristematic zone expansion are both stifled. This study reveals the ZmmiR169q/ZmNF-YA8 module's involvement in maintaining an equilibrium in bestowing plant salt tolerance and root growth and development under salt stress, providing new insights into the molecular mechanism underlying the homeostatic regulation of plant development in response to salt stress.